GRP78 in Glioma Progression and Therapy: Implications for Targeted Approaches - Yue Yang; Wen Li; Yu Zhao; Minxuan Sun; Feifei Xing; Jiao Yang; Yuanshuai Zhou (Biomedicines, 2025)
Glioma is the most common primary malignant brain tumor, accounting for the majority of brain cancer-related deaths. Considering the limited efficacy of conventional therapies, novel molecular targeted therapies have been developed to improve outcomes and minimize toxicity. Glucose-regulated protein 78 (GRP78), a molecular chaperone primarily localized in the endoplasmic reticulum (ER), has received increasing attention for its role in glioma progression and resistance to conventional therapies. Overexpressed in gliomas, GRP78 supports tumor growth, survival, and therapeutic resistance by maintaining cellular homeostasis and regulating multiple signaling pathways. Its aberrant expression correlates with higher tumor grades and poorer patient prognosis. Beyond its intracellular functions, GRP78’s presence on the cell surface and its role in the tumor microenvironment underscore its potential as a therapeutic target. Recent studies have explored innovative strategies to target GRP78, including small molecule inhibitors, monoclonal antibodies, and chimeric antigen receptor (CAR) T cell therapy, showing significant potential in glioma treatment. This review explores the biological characteristics of GRP78, its role in glioma pathophysiology, and the potential of GRP78-targeted therapy as a novel strategy to overcome treatment resistance and improve clinical outcomes. GRP78-targeted therapy, either alone or in combination with conventional treatments, could be a novel and attractive strategy for future glioma treatment.